”Curiosity enhances our perception” – an efficacious way to learn foreign languages - Weigl, Anna (Glottodidactica, 2017)
As in any human action, motivation is playing a key role in learning foreign languages. There are different types of motivation – one of them is curiosity. Curiosity is one of the strongest motivators, since it is based in the human character. Psychologists call curiosity the core of motivation. In my paper I will address a new learning technique, which consists of two didactic concepts at the same time: Learning by teaching and subject orientated learning. Subject orientated learning means the combination of a specific content to be learnt and a given person.